Effect of Cerium Precursor on the Performance of Pure CeO2 Catalysts for Selective Catalytic Reduction of NO with NH3 - Pan, Wei-Guo; Zhou, Yue; Guo, Rui-Tang; Jin, Qiang; Ding, Cheng-Gang; Guo, Shi-Yi (Asian Journal of Chemistry, 2013)
Pure CeO2 catalysts were prepared from different cerium precursors and their activities for selective catalytic reduction of NO with NH3 were investigated in the presence of O2. The results showed that the catalysts prepared from cerium nitrate have better selective catalytic reduction performance and SO2 resistance. As can be seen from the BET, XRD, TPR, TPD and XPS results, the good performance of the catalysts prepared from cerium nitrate should be resulted from large surface area, good redox ability, high NH3 adsorption capacity and enrichment of Ce3+ on the surface accompanied by an increase of active oxygen content.